REGENERASI SEL LIGAMEN PERIODONTAL DENGAN KOLAGEN SISIK IKAN NILA (Oreochromis niloticus) - Adhalin Fuku Handini; Rosa Pratiwi; Tahta Danifatis Sunnah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background : Regeneration of periodontal ligament cells with tilapia scales collagen (Oreochromis niloticus) is one of the therapies that can be used in the field of periodontics. This review aims to explain the mechanism of periodontal ligament cell regeneration using tilapia scales (Oreochromis niloticus) collagen.Methods : Literature collection is done by selecting journals or articles through PubMed, NCBI, and Google Scholar based on keywords that match the author's criteria.Results : Regeneration of cells using collagen from tilapia scales can be used by using a bone graft technique because fish collagen contains calcium and phosphate that resembles human, namely hydroxyapatite (HAP). Fish scales are an alternative source of type I collagen and have the potential to be an alternative material for bone graft.Conclusions : Regeneration of periodontal ligament cells using tilapia scale collagen can be done using bone graft techniques. Fish scales have many benefits apart from having almost the same content as humans as well as materials that are still easy to obtain and a more economical price to use. The authors suggest that the researchers further conduct further research on the preparation of tilapia scales so that they can be applied in tissue engineering actions in the field of periodonsia.